Assessment of Constraints Faced by Farm Women in Adaptation Strategies towards Climate Change - Pandey, A.; Arya, P. (International Journal of Economic Plants, 2022)
The present study was conducted in Bikaner district of Rajasthan during 2020–21 to identify constraint faced by farm women in adaptation strategies towards climate change. The district is surrounded by Sri Ganganagar district to the North and lies in the Thar Desert. The study was conducted with sample size of 280 farm women. A total of two Panchayat Samities were selected by lottery method i.e., Khajuwala and Kolayat. Thus, a total of four Gram Panchayats was selected for the study. Further, two villages from each Gram Panchayat were selected by simple random sampling method. Hence, a total of eight villages were selected for the present study purpose. Further, Thirty five farm women from each (eight) villages will be selected for the final sample size of the study through random sampling. The primary data was collected personally with the help of an interview schedule which was prepared to identify the socio-economic characteristics, communication characteristics and constraints. Ranking method was used based on percentage of the constraints for the analysis of data. Overall twenty six constraints were listed out. The results of the present study revealed the major constraints faced by farm womenwhichwereinadequate/ limited knowledge concerning climate change and adaptation measures and lack of access to weather forecasting technology (Rank I), Lack of training programs on adaptation to climate programs (Rank II), Lack of knowledge about government policies/programs and poor extension services related to climate change assigned Rank III.